The ‘International University’ in the Age of Globalisation: A Unifier of Knowledge or an Information Factory? - Mehmet, Özay (My University, 2002)
In a small, but insightful book, Civilization on Trial, written more than half a century ago, the great English historian, Arnold Toynbee, expressed great pessimism about the prospects of Western civilisation which he found to be Eurocentric (Toynbee, 1948). Toynbee's study of history was universalistic, reflecting a deep knowledge and respect for non-Western cultures and civilisations. For Toynbee history was unified whole; it was a universal history of the entire humanity, not just of some Western people. In this sense, Toynbee is similar to the great Muslim scholar, Ibn Khaldun, the author of Muqaddimah, written almost six centuries ago, as an inquiry into the causes of the rise and decline of civilisations (Mehmet, 1990: 81–4). © 2002, MCB UP Limited